ANALISIS USAHA TANI TERPADU SAPI POTONG DAN PADI SAWAH KELOMPOK TANI â€œKEONG MASâ€ KECAMATAN SANGKUB, KABUPATEN BOLAANG MONGONDOW UTARA (STUDI KASUS) - Tumewu, Judi M; Panelewen, V V.J.; Mirah, A D.P. (ZOOTEC, 2014)
ABSTRACT ANALYSIS OF INTEGRATED FARMING SYSTEM BETWEEN BEEF CATTLE AND RICE PADDY IN FARMERS GROUP OF KEONG MAS AT SANGKUB DISTRICT, NORTHBOLAANG MONGONDOW REGENCY (CASE STUDY). Integrated farming system of beef cattle and rice paddy is a combination of beef cattle fattening and rice paddy managed by â€œKeong Masâ€ Farmers Group. Feces and urine of beef cattle were materials to produce an organic fertilizer and paddy rice straw can be used as feed for beef cattle. The combination of fattening beef cattle and rice paddy straw has a purpose to create minimum cost and using of potential local resources. This research purpose was to evaluate the business profit and cost efficiency of â€œKeong Masâ€ integrated farming system. Research method used was study of case and observation as the information for collecting data. The result showed that profit of un-integrated fattening beef cattle were Rp. 9,780,000,- per 8 cattleÂ  per year. Un-integrated rice paddy gave Rp. 12,745,000,- profit per ha per year. The profit of integrated fattening beef cattle was Rp. 83,457,108 per 12 cattle per year and rice paddy was Rp. 90,517,250. Cost efficiency of un-integrated farming system was only 1.16 while integrated farming system gave cost efficiency of 1.49. Therefore, it can be concluded that the integrated farming system of fattening beef cattle and rice paddy in â€œKeong Masâ€ Farmers Group was profitable and efficient. Keywords : integrated farming system, profit, cost efficiency